2003
DOI: 10.22146/gamaijb.5392
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINANTS OF ENTREPRENEURIAL INTENTION: The Case of Norwegian Students

Abstract: This paper aims to identify determinants of entrepreneurial intentions among young people. The empirical basis is Norwegian students, while an objective is also to create a basis for comparative studies among different economic and cultural contexts. Independent variables in the study include demographic factors and individual background, personality traits, and contextual elements like access to capital and information. The individual perceptions of self-efficacy and instrumental readiness are the variables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 17 publications
6
29
1
6
Order By: Relevance
“…Business management students in Ethiopia who have taken entrepreneurship course will report higher entrepreneurship intention than engineering students who have not taken entrepreneurship course. Gender and intention Though according to some researchers, there were no differences in the entrepreneurial intentions of male and female students (Pruett et al, 2009;Indarti and Kristiansen, 2003), many research suggested that entrepreneurial intention vary significantly with gender (Mazzarol et al, 1999;Kolvereid, 1996;Harris and Gibson, 2008;Shay and Terjesen, 2005;Wilson et al, 2004;Ramayah and Harun, 2005). According to Mazzarol et al (1999) females were less likely to be founders of new business.…”
Section: Hypotheses Entrepreneurial Education and Intentionmentioning
confidence: 99%
“…Business management students in Ethiopia who have taken entrepreneurship course will report higher entrepreneurship intention than engineering students who have not taken entrepreneurship course. Gender and intention Though according to some researchers, there were no differences in the entrepreneurial intentions of male and female students (Pruett et al, 2009;Indarti and Kristiansen, 2003), many research suggested that entrepreneurial intention vary significantly with gender (Mazzarol et al, 1999;Kolvereid, 1996;Harris and Gibson, 2008;Shay and Terjesen, 2005;Wilson et al, 2004;Ramayah and Harun, 2005). According to Mazzarol et al (1999) females were less likely to be founders of new business.…”
Section: Hypotheses Entrepreneurial Education and Intentionmentioning
confidence: 99%
“…Understanding the need for achievement according to (Ashar et al, 2014) is one's focus on achievement. Need for achievement results from demographic characteristics and environmental factors (Indarti & Krinstiansen, 2018). This variable indicates whether a person has a tendency to do business or not and shows that the need for achievement has a positive effect on entrepreneurship intention (Remeikiene et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government has a program for increasing entrepreneurship interest in the student that programs are Student Creativity-Entrepreneurship Program), entrepreneurship student program, business plan competition. What programs support student and graduates that are ready to work in the workplace or independently (Indarti & Krinstiansen, 2018). universities are expected to graduate students who already run businesses, this will strengthen the entrepreneurial vision (Remeikiene et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several factors that influence entrepreneurial intentions, as stated by Indarti (2003) that entrepreneurial intentions are influenced by three things: demographic factors and individual backgrounds, personality factors, and finally contextual element factors. Whereas Wijaya (2007) stated that the factors that influence entrepreneurial intentions are five, namely family environment, education, personal values, age, and gender.…”
Section: Introductionmentioning
confidence: 99%